2015
DOI: 10.1095/biolreprod.115.130609
|View full text |Cite
|
Sign up to set email alerts
|

Sperm Factors and Oocyte Activation: Current Controversies and Considerations1

Abstract: The beginning of embryogenesis is preceded by a sequence of events mediated by the release of intracellular calcium in the ooplasm, a multifaceted process known as oocyte activation. It is now well established that a sperm protein factor introduced into the oocyte at the time of gamete fusion is responsible for initiating the cascade of signaling events involved. Several sperm proteins have been hypothesized as the sperm oocyte-activating factor (SOAF) over the years, with phospholipase C zeta 1 (PLCZ1 or PLCz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(28 citation statements)
references
References 75 publications
0
25
0
3
Order By: Relevance
“…Failed fertilization post-ICSI is attributed to the lack or deficiency of sperm-associated oocyte-activating factors (SOAF) (Amdani et al, 2015). SOAF(s) compartmentalize as part of the post-acrosomal sheath of sperm perinuclear theca (PAS-PT) and trigger intracellular Ca 2+ -release upon fusion of spermatozoa/oocyte membranes or insemination of spermatozoa into oocyte (Sutovsky et al 2003).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Failed fertilization post-ICSI is attributed to the lack or deficiency of sperm-associated oocyte-activating factors (SOAF) (Amdani et al, 2015). SOAF(s) compartmentalize as part of the post-acrosomal sheath of sperm perinuclear theca (PAS-PT) and trigger intracellular Ca 2+ -release upon fusion of spermatozoa/oocyte membranes or insemination of spermatozoa into oocyte (Sutovsky et al 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Among these factors, PLCf has emerged as the strongest candidate and several studies have shown the correlation between absence or deficiency of PLCf with failed fertilization in globozoospermic men (Heytens et al, 2009;and Aghajanpour et al, 2011). However, a growing body of evidence has challenged the importance of PLCf as the key SOAF and proposed other candidate proteins, particularly PAWP and TR-KIT, as the major SOAFs (Muciaccia et al, 2010;Aarabi et al, 2014b;Amdani et al, 2015;Nomikos et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Une hypothèse reposerait sur la possibilité d'une liaison de la phospholipase C gamma (PLCγ) à une protéine ovocytaire YAP (yes-associated protein) qui interagirait avec le domaine SH3 (SRC homology 3 domain) de la PLCγ, permettant la synthèse d'IP 3 ( Figure 2). Cependant cette hypothèse reste controversée [4]. En effet, d'autres chercheurs n'arrivent pas à obtenir de telles oscillations calciques avec PAWP [15].…”
Section: Revuesunclassified
“…Ces oscillations seraient déclenchées par un facteur cytosoluble d'origine spermatique, libéré dans le cytoplasme ovocytaire au moment de la fusion des gamètes. Les Anglo-Saxons utilisent le terme SOAF pour sperm oocyte-activating factor, mais l'identité de ce facteur est restée élusive durant de nombreuses années [4]. En 2002, on a proposé la phospholipase C Zeta (PLCζ), une protéine qui chez les mammifères est exclusivement exprimée dans les spermatozoïdes [5].…”
Section: Diagnostic éTiologiqueunclassified
“…Some sperm factors, such as PLC zeta 1 and post-acrosomal WW-domain binding protein, are considered to play an important role in oocyte activation (Amdani, Yeste, Jones, & Coward, 2015;Ross et al, 2008;Yeste, Jones, Amdani, & Coward, 2017). Sperm can also deliver microRNAs or mRNAs to the fertilized oocyte and influence further embryo development (Boerke, Dieleman, & Gadella, 2007;Hamatani, 2012).…”
mentioning
confidence: 99%